Literacy and Research-oriented Cooperative Problem-based Learning Model: Bridging Students' Chemical Literacy to Support Sustainable Education - Faiz Ilham Pratama; Eli Rohaeti; Endang Widjajanti Laksono; Rasamimanana Joronavalona (Universitas Negeri Semarang, 2026)
Sustainable education can be achieved through an innovative learning process, and one way to do so is to use a high-quality learning model. Literacy and Research-Oriented Cooperative Problem-Based Learning (LIRACLE) is a new learning model developed for undergraduate learning. LIRACLE is adapted from Problem-based learning, cooperative learning, research learning, and literacy-oriented learning. This study aims to examine the effect of the LIRACLE learning model on undergraduate students' chemical literacy. The research employed a quasi-experimental, post-test-only control-group design with undergraduate chemistry students. The instrument used is a chemical literacy rubric. The data were analyzed using an independent-samples t-test. The result of the independent sample t-test is the Asymp. Sig. (2-tailed) of 0.000. This result is below 0.05, indicating a significant difference between the groups using the LIRACLE and PBL learning models in chemical literacy skills. These findings indicate that the LIRACLE learning model significantly improves undergraduate students' chemical literacy compared to the PBL model. Therefore, LIRACLE has the potential to support the development of students' chemical literacy in undergraduate learning.